EL ROL DE LOS ACTORES SOCIALES EN LA CONFIGURACIÓN TERRITORIAL DE MOQUEHUE - Celia Viviana Torrens; Elsie Marcela Jurio; Vanesa Yanina Cappelletti; Germán Gabriel Pérez; Daiana Elcira Cara Plá; Gimena Nathalie Cuevas; María Silvina Hauw; Pablo Alejandro Leyes (Boletín Geográfico)
Moquehue is a small mountain settlement located in Aluminé department, Neuquén, Argentina. It aroses in the 40's, as a product of the development of cattle raising and forestation. Since these activities began, the permanent settlement and first commercial activities appeared, in order to cover the new demands. Nature has given the region a beautiful landscape that acquires value since the 70's, when the population of nearby localities began to usufruct tourism in the region. Even though the lands belong to the Provincial State, since 1984 they are under the control of the Pulmarí Interstate Corporation (PIC), which regulates their use. In 1980, tourism was stimulated by state politics that lead to the growth and expansion of Villa Pehuenia and Moquehue, defining a new territorial configuration, in which different social actors have an active role. In the last decade, this dynamism was accentuated in Moquehue, a zone without regulation of the occupation and in an area with limited provision of services. The objective of this paper was the analysis of territorial transformations promoted by social actors that established the current uses of the land and its environmental consequences, considering the role of municipal and provincial government in these transformations. Research includes compilation of information, interviews and field survey of new occupations. This information was digitized. Four relevant social actors are recognized in the development and growth of Moquehue, linked especially to tourism activity: the municipality, that defines parcels for permanent residential use and services; private actors, that increase accommodation supply; historical local people who subdivide and sell land irregularly, and new actors who settle in the area with permanent residence, linked to other activities that made them choose this place because of its environmental values. As a result, zones with different types of transformation are identified, in which these actors have a decisive role giving different characteristics and dynamics to each one. It can be concluded that the development of tourism in this region has promoted the expansion of Villa Pehuenia-Moquehue, however it has not been accompanied by management and ordering politics aimed in order to preserve the environment. Overlapping jurisdictions and land tenure have placed difficulties in control and regulation of urban growth and land use. This is also evidenced by the lack of infrastructure and provision of basic services in order to improve the life quality of the population, and respond to sustained growth and tourism demands.